ORBITAL TRAUMA IN A CHILD WITH RETROBULBAR HEMORRHAGE: Poster Presentation - Case Report - General practitioner - Rachmawati, dr. Anita Dwi (Majalah Oftalmologi Indonesia, 2023)
Introduction : Retrobulbar hemorrhage vision threatening condition associated with cranio- facial trauma. Rapidly fill the orbit and cause an “orbital compartment syndrome” that subsequently cuts off perfusion to vital ocular structures. Treatment must be initiated immidietly to prevent permanent visual loss. Case Illustration : 10-year-old boy, with left eye blurring of vision, swelling and multiple facial injury post motor accident. Visual acuity was perception of light on left eye, 6/5 and right eye with upper and lower lid laceration wounds. He had a dense afferent pupillary defect and the ocular movements of the left eye were limited in all directions of gaze. The orbit was tense with significant resistance to retropulsion. Diagnosed with acute retrobulbar haemorrhage following blunt trauma with medial wall fracture. Intravenous acetazolamide and timolol was commenced continued with emergency lateral canthotomy. His vision immediately improved to 6/60 and 3 hours later was 6/18. He was treated for left traumatic optic neuropathy with IV Mehtylprednisolone for 3 days followed two weeks oral prednisolone Discussion : Conclusion : Retrobulbar haemorrhage is a vision-threatening emergency often necessitating immediate lateral canthotomy for preservation of vision. In children, as the optic nerve canal is smaller, a lesser volume is available for the nerve to expand, thus early visual impairment could occur following trauma. Prompt recognition and appropriate treatment of this ocular emergency is imperative, for timely management determines the ultimate outcome.